Telomere Length: A Review of Methods for Measurement - Montpetit, Alison J. (Nurs Res, 2014)
BACKGROUND: The exciting discovery that telomere shortening is associated with many health conditions, and that telomere lengths can be altered in response to social and environmental exposures, has underscored the need for methods to accurately and consistently quantify telomere length. OBJECTIVES: The purpose of this paper is to provide a comprehensive summary that compares and contrasts the current technologies used to assess telomere length. DISCUSSION: Multiple methods have been developed for the study of telomeres. These techniques include quantification of telomere length by terminal restriction fragmentation—which was one of the earliest tools used for length assessment—making it the gold standard in telomere biology. Quantitative-PCR provides the advantage of being able to use smaller amounts of DNA, thereby making it amenable to epidemiology studies involving large numbers of people. An alternative method uses fluorescent probes to quantify not only mean telomere lengths, but also chromosome-specific telomere lengths; however, the downside of this approach is that it can only be used on mitotically active cells. Additional methods that permit assessment of the length of a subset of chromosome-specific telomeres, or the subset of telomeres that demonstrate shortening, are also reviewed. CONCLUSION: Given the increased utility for telomere assessments as a biomarker in physiological, psychological and biobehavioral research, it is important that investigators become familiar with the methodological nuances of the various procedures used for measuring telomere length. This will ensure that they are empowered to select an optimal assessment approach to meet the needs of their study designs. Gaining a better understanding of the benefits and drawbacks of various measurement techniques is important not only in individual studies, but also to further establish the science of telomere associations with biobehavioral phenomena.